PENGARUH INDIKATOR MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN (Students' Journal of Accounting and Banking, 2013)
This study aims to examine the influence of the board of directors, independent directors, institutional ownership, and debt to equity on firm performance. Corporate governance controls to create mechanisms and tools to enable the creation of a balanced system of profit sharing to stakeholders and create efficiencies for the company.In this study, researchers used a population of manufacturing firms over the period 2009-2011. The method used was purposive sampling method and the method of data collection using the documentation. Samples obtained in this study 89 manufacturing companies. Test tool in this study using multiple linear regression, partial test (t test), and a simultaneous test (F test).Results of this study are significant negative effect board, proportion of independent board significant positive effect, negative effect of institutional ownership is insignificant, debt to equity significant negative effect, firm size is not significantly negative, and the composition of assets and a significant positive effect on firm performance.Keywords: Number of board of directors, the proportion of independent directors, instituional ownership, debt to equity, firm size, asset composition and firm performance